An Update of Cutaneous Melanoma Patients Treated in Adjuvancy With the Allogeneic Melanoma Vaccine VACCIMEL and Presentation of a Selected Case Report With In-Transit Metastases - Mordoh, Ana; Aris, Mariana; Carri, Ibel; Bravo, Alicia Inés; Podaza, Enrique; Pardo, Juan Carlos Triviño; Cueto, Gerardo Rubén; Barrio, María Marcela; Mordoh, José (Frontiers in Immunology, 2022)
The CSF-470 vaccine (VACCIMEL) plus BCG and GM-CSF as adjuvants has been assayed in cutaneous melanoma patients. In the adjuvant randomized Phase II study CASVAC-0401, vaccinated patients had longer distant-metastases-free survival (DMFS) than those treated with IFNα2b. Five years after locking the data, an actualization was performed. The benefit in DMFS was maintained in the vaccinated group versus the IFNα2b treated group (p=0.035), with a median DMFS of 96 months for VACCIMEL and 13 months for IFNα2b. The favorable risk-benefit ratio was maintained. DMFS was also analyzed as a single cohort in all the IIB, IIC and III patients (n=30) who had been treated with VACCIMEL. The median DMFS was 169 months, and at 48 months follow-up it was 71.4%, which was not statistically different from DMFS of previously published results obtained in adjuvancy with ipilimumab, pembrolizumab, nivolumab or dabrafenib/trametinib. The possible toxicity of combining VACCIMEL with anti-immune check points inhibitors (ICKi) was analyzed, especially since VACCIMEL was co-adjuvated with BCG in every vaccination. A patient with in-transit metastases was studied to produce a proof of concept. During treatment with VACCIMEL, the patient developed T-cell clones reactive towards tumor-associated antigens. Three years after ending the VACCIMEL study, the patient progressed and was treated with ICKi. During ICKi treatment, the patient did not reveal any toxicity due to previous BCG treatment. When she recurred after a 4-year treatment with nivolumab, a biopsy was obtained and immunohistochemistry and RNA-seq were performed. The tumor maintained expression of tumor-associated antigens and HLA-I and immune infiltration, with immunoreactive and immunosuppressive features. VACCIMEL plus BCG and GM-CSF is an effective treatment in adjuvancy for stages IIB, IIC and III cutaneous melanoma patients, and it is compatible with subsequent treatments with ICKi.